Kompetensi Auditor, Independensi Auditor, Pengalaman Auditor, Etika Auditor dan Kualitas Audit - Wasiah, Khikmatul; Wahyuningsih, Panca (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2024)
This research aims to test and analyze whether auditor competence, auditor independence, auditor experience and auditor ethics have an effect on audit quality. The population in this study were auditors who worked in Public Accounting Firm in Semarang. Sampling was carried out using the census method and the number of samples was 73 respondents. The type of data used is primary data. This study uses a questionnaire in collecting data. The test techniques used are validity test, reliability test, classic assumption test including normality test, multicollinearity test and heteroscedasticity test. Hypothesis testing in this study used multiple linear tests with SPSS version 26. The results of this study indicate that Auditor Competence has a negative and insignificant effect on Audit Quality. Meanwhile, Auditor Independence has a positive and insignificant effect on Audit Quality. Auditor experience has a positive and significant effect on audit quality. Auditor Ethics has a positive and significant effect on Audit Quality. Keywords: Auditor Competence, Auditor Independence, Auditor Experience, Auditor Ethics and Audit Quality.